Traditional Leaders and the Legality of Punishment for Violence in the Indonesian Criminal Justice System - Muh. Rafli Basri; Fenty U. Puluhulawa; Irlan Puluhulawa (The Easta Journal Law and Human Rights, 2026)
This study aims to analyze the position of customary officials and the legality of violent sanctions within the Indonesian criminal justice system. The research problem arises from the continued existence of customary punishment practices involving physical and psychological violence in customary law communities, while national criminal law establishes the state as the sole institution authorized to impose criminal penalties. This study employs a normative legal method with legislative, conceptual, and case-based approaches through a literature review of primary, secondary, and tertiary legal sources. The findings indicate that traditional officials possess sociological and constitutional legitimacy in maintaining order within traditional communities; however, their authority remains limited by the principle of legality and the protection of human rights. Restorative customary sanctions remain acceptable as long as they do not violate fundamental individual rights, whereas sanctions involving elements of violence can still be classified as criminal offenses under the Criminal Code. This study underscores the importance of harmonizing customary law with national criminal law through the strengthening of a restorative justice approach and the establishment of regulations that clearly define the limits of the authority of customary institutions.